Formulation of Nifedipine–Polyvinyl Pyrrolidone (PVP) Solid Dispersion System and Intrinsic Dissolution Rate Evaluation - Riza Maulana; Henry Harto; Tiara Dewi Salindri Pratama (Pharmacon: Jurnal Farmasi Indonesia, 2022)
Nifedipine is a drug that acts as an antihypertensive and anti-angina. Nifedipine is known as a drug with poor water solubility. This characteristic will affect the intrinsic dissolution rate so that it can affect the absorption process and reduce the amount of drug that reaches systemic circulation. One of the strategies to increase the intrinsic dissolution rate is developing nifedipine to solid dispersions form. This study aims to observe the intrinsic dissolution rate of nifedipine after it has been made into a solid dispersion. Four samples were prepared, including three solid dispersions of nifedipine-PVP K-30 and one sample of pure nifedipine. The results of the intrinsic dissolution tests are then interpreted through the intrinsic dissolution rate constant (G). The solid dispersions with concentration of nifedipine-PVP K-30 90%:10%; 75%:25%; 60%:40% (w/w), and pure nifedipine produced G values of 3.63; 9.33; 12.63; and 2.08 µg/mm2. min1, consecutively. It shows that the formulation of nifedipine-PVP K-30 solid dispersions has higher G values than pure nifedipine. In addition, increasing PVP K-30 concentration up to 40 % (w/w) can increase the intrinsic dissolution rate of the nifedipine-PVP K-30 solid dispersion system.